Plurality and Fragmentation in Social Work: Analyzing the Implications of Flexner Using a Philosophy of Science Perspective. (13th July 2016) - Brady, Shane R.; Moxley, David
ABSTRACT: The authors examine how the profession's adaptation to Flexner's criteria influences the emergence of the neomedical model as the majoritarian paradigm within social work even in the face of a pluralism manifest by the existence of other competing paradigms. One endorses empowerment in social work, and the other embraces societal transformation in radical terms. Given this pluralism, we consider how fragmentation exists within the profession, such that two scenarios are useful in considering how social work will evolve as a profession: (a) seeking unity with a majoritarian paradigm in ascendancy as it attempts to co-opt the other two paradigms; or (b) fragmenting into multiple entities each with its own stance on society, theory of social issues, and models of practice.